Detection of Escherichia coli in biofilms from pipe samples and coupons in drinking water distribution networks - Juhna, T. (2007)
Fluorescence in situ hybridization (FISH) was used for direct detection of Escherichia coli on pipe surfaces and coupons in drinking water distribution networks. Old cast iron main pipes were removed from water distribution networks in France, England, Portugal, and Latvia, and E. coli was analyzed in the biofilm. In addition, 44 flat coupons made of cast iron, polyvinyl chloride, or stainless steel were placed into and continuously exposed to water on 15 locations of 6 distribution networks in France and Latvia and examined after 1 to 6 months exposure to the drinking water. In order to increase the signal intensity, a peptide nucleic acid (PNA) 15-mer probe was used in the FISH screening for the presence or absence of E. coli on the surface of pipes and coupons, thus reducing occasional problems of autofluorescence and low fluorescence of the labeled bacteria. For comparison, cells were removed from the surfaces and examined with culture-based or enzymatic (detection of β-d-glucuronidase) methods. An additional verification was made by using PCR. Culture method indicated presence of E. coli in one of five pipes, whereas all pipes were positive with the FISH methods. E. coli was detected in 56% of the coupons using PNA FISH, but no E. coli was detected using culture or enzymatic methods. PCR analyses confirmed the presence of E. coli in samples that were negative according to culture-based and enzymatic methods. The viability of E. coli cells in the samples was demonstrated by the cell elongation after resuscitation in low-nutrient medium supplemented with pipemidic acid, suggesting that the cells were present in an active but nonculturable state, unable to grow on agar media. E. coli contributed to ca. 0.001 to 0.1% of the total bacterial number in the samples. The presence and number of E. coli did not correlate with any of physical and/or chemical characteristic of the drinking water (e.g., temperature, chlorine, or biodegradable organic matter concentration). We show here that E. coli is present in the biofilms of drinking water networks in Europe. Some of the cells are metabolically active but are often not detected due to limitations of traditionally used culture-based methods, indicating that biofilm should be considered as a reservoir that must be investigated further in order to evaluate the risk for human health.